Prevalence of parenthood among hospitalized adult patients with severe mental illness: a quantitative data analysis - Havelková, Anna; Havelka, David; Koros Bartošová, Kateřina (Frontiers in Psychiatry, 2024)
In the Western world, more than one-third of the patients of productive age hospitalized for severe mental illness (SMI) are parents. Each of their offspring is exposed to several stressors related to their parent's illness and hospitalization, which puts them at an increased risk of developing mental health problems. In the Czech Republic, no statistics are currently available about the families of patients with SMI, inpatients who are parents, or data about their children (ages ≤18 years). Therefore, our research aim was to describe the prevalence of parenthood among hospitalized patients with SMI, assess the number of children and determine the extent to which offspring information was present in medical records.Quantitative data from medical records (2,768 patients, aged 18-63 years, hospitalized for SMI between 2017 and 2020) from two large inpatient psychiatric facilities were examined. Parental information, demographic characteristics, number of children, and other available data were collected. The prevalence of parenthood among inpatients with SMI was 34.6%. Parenthood was most prevalent among female patients and patients with recurrent depressive and bipolar disorders. The total number of offspring in 957 patient-parents was 1781 (41.7% minors under the age of 18). Information on parenthood was available in 99.7% of cases; information on the age of offspring, custody, and sociodemographic situation varies, being included in 73% to 89.7% of the medical records (some details were more frequently recorded than others). The data obtained may help to better understand and address the specifics of these families and thus serve as a basis for the development of prevention programs.